"Being Scorned by One's Own is Perfect Joy": The Strange Case of Dorothy Day. (December 2013) - Phillips, Jacob
<x xml:space="preserve">Abstract</x> Dorothy Day has long been seen as an enigma in understandings of twentieth‐century American Catholicism. With the publication of Dorothy Day's extensive letters and diaries in 2008, the enigmatic character of Day's relation to various fault lines of Catholic identity has been made even more apparent. Day's ability to sidestep received opinion, in order to disclose (arguably) something of an inner resonance between apparently differing viewpoints, often left her sitting uneasily with the proponents of different positions across the spectrum of Catholic thinking, causing her to quote St Francis, saying that "being scorned by one's own is perfect joy." This review article gives a summary of the contributions made by these volumes to understandings of Day's life and work, before discussing three particular fault lines, where Day's ability to straddle differing positions is most perceptible: her practice of pre‐Conciliar spirituality, her attitude to ecclesiastical authority, and her position on matters pertaining to gender and sexuality.